Quantitative analysis of metals in waste foundry sands by calibration free-laser induced breakdown spectroscopy - Diaz Pace, Diego Martin (2017)
Laser-induced breakdown spectroscopy (LIBS) was applied for quantitative analysis of the elemental composition of waste molding and core sands produced from industry as part of the casting process. To perform the analysis, waste foundry sands (WFS) were collected from metalcasting foundries and prepared in the form of solid pellets with the addition of polyvinyl alcohol as binder. The measurements were carried out using the Mobile double pulse instrument for LIBS analysis (Modì). The spectral analysis was carried out with the calibration-free approach (CF-LIBS). Metal elements commonly found in WFS including Al, Ba, Fe, Li, Mg, Mn, Pb, Ti, Zr, and Zn, were detected and quantified. The metal concentrations for WFS were compared with virgin sand to assess the influence of the casting material as well as the binders used in the foundries to reclaim the sands. The results demonstrated the feasibility of LIBS method as an alternative or complementary technique for the chemical characterization of WFS.